Pemberdayaan Kelompok Wanita Tani “Tirto Mekar Tani” melalui Penerapan Teknologi Budidaya Hidroponik di Desa Tamantirto, Bantul - Bambang Sriwijaya; Umul Aiman; Farah Nur Syafi'ah Wijayanti (Universitas Perjuangan Tasikmalaya, 2026)
This community service program aims to enhance the capacity and self-reliance of the “Mekar Tani” Women Farmers Group (KWT) in Tamantirto Village, Kasihan District, Bantul Regency through the application of hydroponic cultivation technology. The program was motivated by limited agricultural land in semi-urban areas and the need for efficient, environmentally friendly, and economically valuable food production alternatives. The implementation included technical training, business management assistance, and participatory monitoring and evaluation, using a hands-on approach to accelerate participants’ understanding of hydroponic systems. The training focused on assembling simple hydroponic systems, preparing plant nutrients from local materials, and maintaining production and financial records for microenterprises. The results showed an average 25% improvement in participants’ technical and managerial understanding. The hydroponic systems achieved a planting success rate above 90%, with average yields per plant of 98.56 g for pakcoy, 81.21 g for lettuce, and 40.12 g for mustard greens. The activity also strengthened self-reliance, group solidarity, entrepreneurial awareness, and innovation capacity among KWT members. Overall, this program contributes to household food security and promotes sustainable local economic development, demonstrating the potential of participatory hydroponic technology in empowering rural women.